Temperature fluctuations within and outside a silo with treated termite mound clay as construction material (2007)
Elevated temperatures and excessive fluctuations -within a grain silo result in condensation of moisture on the inner wall surfaces and its migration within the grain bulk, leading to moulding and caking. There is the need to identify appropriate materials for silo construction that will minimize temperature fluctuations and reduce grain spoilage on storage. A 5.6m3 grain silo construction from 15mm-thick treated termite mould clay bricks tested for temperature fluctuations. Morning, afternoon and evening temperatures, and the maximum and minimum temperatures recorded over a 24hr period within and outside the silo were monitored for 60 days. The walls were physically examined for possible moisture condensation. The maximum and minimum temperatures recorded within the silo were 20°C and 30°C, respectively as against 21°C and 36°C for the ambient. The average temperature fluctuation within the silo was 9.5°C as against 10.3°C for the ambient. The temperature within and outside the silo were quite distinct without any overlap. There was no sign of moisture condensation on the wall surfaces. Grain silo constructed from termite mound clay have the potential to reduce the temperature fluctuations within the silo, eliminate moisture condensation and reduce grain spoilage.